Generalized Joint Laxity Is Associated With Dynamic Hip Ultrasonography Measures in Female Athlete Patients Who Are Not Hypermobile. (20th December 2021) - Stracciolini, Andrea; Yen, Yi‐Meng; Miller, Patricia E.; Whitney, Kristin E.; Jones, Jacob; Novais, Eduardo N.; d'Hemecourt, Pierre A.
Abstract : Objectives: To investigate ultrasound (US) femoroacetabular translation measurements in female athlete patients. Methods: A prospective cross‐sectional study was conducted in female athlete patients <50 years. Demographic data, Beighton score/hypermobility status, and sport participation were collected. Hip dysplasia was determined using radiographic measurements (lateral center edge angle, anterior center edge angle, Tönnis angle); femoral version angles were measured with CT or MR. Femoroacetabular translation US measures included neutral (N), neutral flexed (NF), extension external rotation/apprehension (EER) positions. Maximal difference (delta) between US measures was calculated. Results: 206/349 female hips were analyzed (median age 21.2 years [range, 12–49.5]). The primary sport group was performing arts (45%, 92/206). Mean Beighton score was 5.2 (SD, 2.5) with 61% (129/206) of hips exhibiting hypermobility (Beighton score ≥5). For each additional unit of Beighton score, N US measurement increased by 0.7 mm ( β = 0.7; 95% confidence interval [CI] = 0.22–1.25; P < .001), NF by 1 mm ( β = 0.9; 95% CI = 0.3–1.43; P = .002) and EER by 0.8 mm ( β = 0.8; 95% CI = 0.27–1.37; P < .001) when adjusting for age and dysplasia status. A positive correlation was detected between NF ( r = 0.19; 95% CI = 0.05–0.33; P = .007) and EER ( r = 0.19; 95% CI = 0.05–0.32; P = .01) with Tönnis angle and a negative correlation between the delta and femoral version ( r = −0.20; 95% CI = −0.35 to 0.03; P = .02). No difference in US measures was detected across sport groups (N [ P = .24], NF [ P = .51], EER [ P = .20], delta [ P = .07]). Conclusion: Beighton score was independently associated with dynamic US measures in female athlete patients who are not hypermobile when controlling for other factors.